Determination of background indoor air pollutants and thermal comfort in faculty of earth science building. Issue 1 (August 2021) - Awang, N R; Radzi, N A N M; Yong, T S; Abas, M A; Zainordin, N S; Ramli, N A; Ibrahim, N
Abstract: The focus of this study was to determine the most significant factors that influencing indoor air quality (IAQ) and thermal comfort of a mechanically ventilated lecturer office room in FSB new building. This study measured the concentrations of ozone (O3 ), nitrogen dioxide (NO2 ), total volatile organic compound (TVOC), carbon dioxide (CO2 ), carbon monoxide (CO), particulate matter (PM), temperature and relative humidity using seven set up conditions. The set-up condition for study room is based on temperatures that have been selected between 22°C to 26°C and window of the room being either close or open. The IAQ were analyzed by descriptive analysis to indicate the parameters variations. Furthermore, thermal comfort for the room of FSB new building has been determine by the CBE thermal comfort tool based on ASHRAE 55 standards. Result suggested that the IAQ of the studied room in FSB new building showed maximum reading during the window was opened condition. The setup of selected temperature air conditioner was minimizing the concentrations of IAQ because IAQ were increase during high temperature. Among of the selected IAQ parameters, particulate matter was the most significant indoor air pollutants in the studied room with the highest average concentration was 20.944 μg/m 3 . The increment of particulate matter concentrations was due to the suspended dust in the room and additional movements of the occupants inside the room exaggerate the condition. Besides, results of this study suggested that a good IAQ inside an air conditioning room was achieved when the temperature is set at 26°C.